Internasionalisasi Kota: Gorontalo, Berkearifan Lokal Berwawasan Global - Marzaman, Atika (Gorontalo Journal of Government and Political Studies, 2018)
The open access to information and the rapid turnover of goods and services encourages the city to emerge as one of the actors in international relations. Not only that, cities in different parts of the world can compete instantly without any obstacles. The current phenomenon is that cities interact directly, establishing cooperative relationships in commerce, government, education, as well as in peace building missions.This research is trying to study Gorontalos potential to become an international region with the development of global cooperation. This research is done by qulitative method through interview and literature source search. With the potential and a very strategic location Gorontalo has a great opportunity to cooperate with other regions in various parts of the world. This study try to assess Gorontalos capacity to internationalize itself. Using the data obtained this research analyze the opportunities and challenges faced in the internationalization process of Gorontalo City.The results show that regionalization through an international cooperative model actually offers a bright prospect. However, institutional obstacles need to be responded by local and central government through strengthening the leadership and capacity of the government, providing clear rules of law, supervision in policy implementation and adequate funding.